Rationalizing the Phenomenon of Converting Hindu Temples into Mosques (Merasionalkan fenomena menukaran kuil Hindu ke dalam) - Omer, Spahic (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract In this paper, some aspects of the phenomenon of reclaiming and converting Hindu temples into mosques, following the arrival of Islam and Muslims to the Indian shores, are discussed. The underlying reasons for the phenomenon which were not only of expedient socio-economic and political, but also of profound spiritual nature, are the focus of discussion. The main thrusts of the paper revolves around the issues pertaining to the expediency of converting temples into mosques, Muslim general tolerance towards conquered peoples, converting temples into mosques as a relative and qualified trend, as well as the relationship between converting temples into mosques and the evolution of the identity of Islamic architecture. The nature of the paper is conceptual or philosophical, rather than empirical. Keywords: Hindu Temples, Mosques, India, Islam, Muslims, Islamic Architecture. Abstrak Kajian ini memperbincangkan beberapa aspek fenomena menuntut kembali dan menukar tokong Hindu ke masjid selepas ketibaan Islam dan umat Islam ke tanah India. Fokus perbincangan ialah dasar alasan fenomena yang bukan sahaja bermanfaat untuk sosio-ekonomi dan politik, tetapi juga alam rohani yang mendalam. Kajian ini berkaitan dengan isu-isu seperti kesesuaian menukar tokong ke masjid, toleransi umum orang Islam terhadap orang ditawan, menukar tokong ke masjid sebagai trend relatif dan berkelayakan, serta hubungan antara tokong-tokong hindu yang ditukar menjadi masjid dan evolusi identiti seni bina Islam. Kajian ini berunsurkan konsep atau falsafah, dan bukan empirikal. Kata Kunci: Tokong Hindu, Masjid, India, Islam, Muslim, Seni Bina Islam.